SURGICAL CORRECTION OF ACCOMPANYING PATHOLOGY THE ORGANS OF ABDOMINAL CAVITY UNDER LAPAROSCOPIC CHОLECYSTECTOMY - Bychkov, S.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Author brings the experience of making 162 simultaneous operations with the use of laparoscopic technologies at combination of cholecystolithiasis with other diseases the organs of abdominal cavity. Author made the following conclusions: at combination of cholecystolitiasis with other pathology from the part of abdominal cavity there is a possibility of making simultaneous laparoscopic operation that allow to relieve the patient from risk of repeated surgical aggression; the invented methods of laparoscopic criovagotomy and transplantations of islandal cells of pancreas are efficient in treatment of peptic ulcer of duodenum and in achievement of durable compensation of diabetes mellitus.